Do students perform better under pressure? The relationship of flow experiences to cramming in undergraduate students - Alea, Ailene L.; Chan, Tiffany G.; Mateo, Leenard Niño O. (2010)
This study is about the relationship of Flow Experience to the persistence of Cramming. Following Csikszentmihalyi's optimal flow, when skill-challenge imbalance is present, a student may delay working on a task until the eleventh hour to increase the task's level of interestingness. The respondents were senior Communication students of UPVTC and LNU. They were classified as either Chronic or Moderate Crammer and With or Without Flow Experience, using the Cramming Questionnaire and Flow Experience Questionnaire, respectively. The Chronic Crammers With Flow were asked to answer the Subjective Experience of Flow and Cramming Questionnaire. Through the Chi-Square test of independence, the null hypothesis was accepted which meant that flow experience is not a significant factor in the persistence of cramming. However, it was discovered that the persistence of procrastination and cramming is not always a function of negative causes. Some Chronic Crammers cram, although few, because they experience flow in cramming.
Undergraduate thesis (B.A.S.S. Psychology)--University of the Philippines, Tacloban
Keywords: College students -- Philippines; Procastination